Progressive hemorrhagic intracranial dermoid cyst: A case report with imaging and diagnostic considerations - Parisa Pishdad, MD; Amirhossein Soltani, MD; Shakiba Houshi, MD; Mohsen Salimi, MD (Radiology Case Reports)
This report describes the case of a 35-year-old woman with a recurrent ruptured intracranial dermoid cyst. These rare congenital lesions account for less than 1% of intracranial tumors globally. The patient was first diagnosed in her adolescence and underwent surgical excision with shunt placement at the age of 23, which provided symptom relief for 6 years. Her symptoms later recurred, including headaches, blurred vision, and progressive weakness. Imaging revealed a hemorrhagic lobulated mass that compressed the brainstem, encased vascular structures, caused a midline shift, and led to ventricular dilation. These findings suggested possible incomplete removal of the cyst wall during the initial surgery. This case highlights the challenges of diagnosing and managing recurrent intracranial dermoid cysts. It emphasizes the need for long-term monitoring, detailed imaging to assess recurrence and complications, and a multidisciplinary approach to treatment to improve outcomes.